ANALISIS KENDALI INDUSTRIALISASI MODEL SUMBER DAYA HUTAN DALAM MENDUKUNG SDGs EKOSISTEM DARATAN - Nilwan Andiraja (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2026)
Forests are one of Indonesia’s and the world’s most valuable assets that must be preserved. Protection can be achieved through various means to ensure forests retain their resources and produce them. Furthermore, efforts are also needed to avoid threats from their surroundings. One obvious threat to forest resources is industrialization. This study aimed to examine mathematical control models for preventing forest resource depletion due to industrialization. In this study, a new mathematical model was developed by modifying the previous model by adding government industrialization controls. A new objective function was then developed to analyze the forest resource classes after they were controlled. Optimal control was obtained using the Pontryagin Principle, followed by numerical simulations. The results of the numerical simulations showed that forest resource density did not decrease and even increased despite the depletion of forest resources due to industrialization. Therefore, forest resource protection and SDGs 15 (terrestrial ecosystems) can be achieved if Industrialization is controlled by the government.